Gambaran Profil Lipid Pasien Infark Miokardium Akut di RSUD DR. H. Abdul Moeloek Lampung tahun 2021 - Kevin Jeremia Purba; agustyas tjiptaningrum; syazili mustofa (Medula, 2023)
Acute myocardial infarction (AMI) is a condition in which the myocardium or heart muscle necrotizes as a result of a sudden lack of oxygen in the heart caused by atherosclerosis as the result of embolism or total thrombus. The risk factor of the disease is Dyslipidemia, characterized by disturbed lipid profiles such as decreasing of high density lipoprotein (HDL), increasing of low density lipoprotein (LDL), total cholesterol, and triglycerides. This study is usefull for understanding and describing the lipid profile in AMI patients at RSUD DR. H. Abdul Moeloek Lampung Province in 2021. This descriptive study used a cross-sectional research design and was conducted in the Medical Records section of RSUD DR. H. Abdul Moeloek Lampung Province. The results of this study showed that the dominant sex group was male with a total of 50 (79.4%) people. The dominant age group is the 56-65 year age group with a total of 27 (42.9%) people. The largest group of occupation were farmers with 11 (17.5%) people. The group with the most HDL cholesterol level was in the low limit (<40 mg/dl) as many as 31 (49.2%) people. The group with the highest LDL cholesterol level was in the optimal category (<100 mg/dl) of 24 (38.1%) people. The group with the highest triglyceride level was in the optimal category (<150 mg/dl) with a total of 38 (60.3%) people. The group with the highest total cholesterol level was in the optimal category (<200 mg/dl) with 41 people (65.1%). The group with the highest LDL/HDL cholesterol ratio was in the low category (<44) with 56 people.